Case report: A novel de novo germline loss-of-function mutation in the STAT1 transactivation domain in two Chinese siblings, with the elder sibling presenting with multifocal Bacillus Calmette–Guerin osteomyelitis - Lim, Qin Ying; Leung, Daniel; Lam, Crystal K.; Yang, Xingtian; Cheong, Kai N.; Yik, Andrew K. H.; Yang, Jing; Chan, Koon-Wing; Lee, Pamela P. W.; Tsumura, Miyuki; Au, Elaine Y. L.; Rosa Duque, Jaime S.; et al. (Frontiers in Immunology, 2025)
Signal transducer and activator of transcription 1 (STAT1) gene mutations have broad clinical phenotypes, classified by the inheritance pattern and functional state. Individuals with autosomal dominant STAT1 deficiency are more susceptible to intracellular bacteria, the hallmark of which is Mendelian susceptibility to mycobacterial diseases (MSMDs) that are associated with increased risks of invasive disease by weakly virulent mycobacteria. We report a novel de novo heterozygous missense mutation in exon 23 of the STAT1 gene (NM_007315.4):c.2129C>T(p.Ser710Phe) (S710F), located in the transactivation domain (TAD) for two Chinese siblings, whereby the index patient presented with multifocal osteomyelitis after Bacillus Calmette–Guerin (BCG) vaccine, while the younger sibling was spared the infection, as BCG vaccination was withheld at birth. STAT1 loss-of-function was confirmed by the gamma-activated sequence reporter assay, representing the first loss-of-function mutation in the TAD of the STAT1 gene. Both parents did not have the same mutation, and this finding is suggestive of gonadal mosaicism.